2013
DOI: 10.1002/hast.159
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Sin: The Ethics of Vaccines Against Smoking

Abstract: Advances in immunotherapy are paving the way toward vaccines that target unhealthy behaviors, such as a vaccine that blocks the action of nicotine, reducing the pleasure caused by smoking. Such a tool could prove to be an effective tool for preventing children from taking up smoking. Would it be permissible?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Pharmaceutical companies have developed and tested three nicotine vaccines: NicVAX, CYT002-NicQb, and TA-NIC (Cornuz et al, 2008;Goniewicz & Delijewski, 2013;Lieber & Millum, 2013). Clinical trials have been carried out to study the effectiveness of these vaccines on adults as a smoking cessation tool.…”
Section: Effectiveness Of Nicotine Vaccinesmentioning
confidence: 99%
See 4 more Smart Citations
“…Pharmaceutical companies have developed and tested three nicotine vaccines: NicVAX, CYT002-NicQb, and TA-NIC (Cornuz et al, 2008;Goniewicz & Delijewski, 2013;Lieber & Millum, 2013). Clinical trials have been carried out to study the effectiveness of these vaccines on adults as a smoking cessation tool.…”
Section: Effectiveness Of Nicotine Vaccinesmentioning
confidence: 99%
“…Clinical trials have been carried out to study the effectiveness of these vaccines on adults as a smoking cessation tool. They have passed phase I and II testing by showing a positive efficacy, identification of side effects, and by determination of appropriate dosages (Lieber & Millum, 2013). Experimental studies indicated that after 12 months of providing the nicotine vaccines for adult smokers, smoking cessation rates were between 16-42%, depending on the type and dose of vaccines (Cornuz et al, 2008;Lieber & Millum, 2013).…”
Section: Effectiveness Of Nicotine Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations